Adorno, Lukács and the metaphysical forms of Marxist Philosophy - Escuela Cruz, Chaxiraxi M.ª (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This paper presents a comparative account of the respective developments of Th. W. Adorno’s and G. Lukács’ rescue of Marxist Philosophy. It is important how they utilize the notion of reification and commodity fetishism to articulate their theories of social domination.
Keywords: Adorno; reification; emancipation; Lukács; Marx; materialism; Commodity